The equatorial stratospheric QBO and geomagnetic activity - Zossi Artigas, Marta Maria (2005)
The quasi-biennial oscillation (QBO) of the zonal wind in the equatorial stratosphere is analyzed in connection to geomagnetic activity as measured by the disturbance storm time (Dst) index. A running correlation between Dst band pass filtered values, and the equatorial zonal wind at 15, 20 and 30 hPa was estimated. Although not as clear as in the case of F10.7 analyzed in a previous work, an oscillation of around 11 years can be noticed in the running correlation coefficients, with maximum positive and negative values during maximum and minimum solar activity levels, respectively. Taking into account that higher negative Dst values correspond to stronger geomagnetic storms, this means that during maximum solar activity, there is higher (lower) geomagnetic activity during the QBO easterly (westerly) phase. During minimum solar activity this relationship is reversed. A link between these results and geomagnetic activity effects over atmospheric dynamics in the Northern Polar stratosphere is suggested.